Influence of biochar content on structure and photocatalytic activity of TiO₂/g-C₃N₄/biochar composite materials - Nguyễn, Thanh Tươi; Bùi, Thị Minh Nguyệt; Nguyễn, Minh Luôn; Nguyễn, Văn Hưng (Hue University Journal of Science: Natural Science, 2025)
In this study, a ternary composite material TiO₂/g-C₃N₄/biochar (TCNBC), derived from reed stalks, was successfully synthesised by using a simple hydrolysis method. The study demonstrates that biochar has a significant impact on the structure and photocatalytic activity of the obtained composite. Biochar plays a crucial role in inhibiting crystal growth, increasing the specific surface area, reducing the band gap energy, and enhancing the visible light absorption capability of TiO₂. The TCNBC composite exhibits an average crystal size of 5.5 nm and a lower band gap energy of 0.62 eV, while its specific surface area (32.6 m²/g) is significantly higher than that of pure TiO₂ (33.7 nm, 3.02 eV, and 2.1 m²/g). The synthesised photocatalyst composite effectively catalysed the photodegradation of doxycycline (DC) from aqueous solutions. This composite exhibited approximately 7.48 times higher photocatalytic activity compared with pure TiO₂. The TCNBC composite synthesised with a TiOSO₄/g-C₃N₄/biochar mass ratio of 4/1.5/0.5 achieved the highest DC photodegradation efficiency, reaching 91.93% within 120 minutes of visible light irradiation. These findings indicate that the synthesised catalyst holds great promise for the treatment of DC in wastewater.